2013
DOI: 10.1007/s00005-013-0263-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glycogen Synthase Kinase 3-β in Immunity and Cell Cycle: Implications in Esophageal Cancer

Abstract: Esophageal cancer (EC) is one of the most aggressive gastrointestinal malignancies, possessing an insidious onset and a poor prognosis. Numerous transcription factors and inflammatory mediators have been reported to play a pivotal role in the initiation and progression of this cancer. However, the specifics of the signaling network responsible for said factors, especially which elements are the critical regulators, are still being elucidated. Glycogen synthesis kinases 3 (GSK3)b was originally regarded as a ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 171 publications
(173 reference statements)
0
10
0
Order By: Relevance
“…Esophageal cancer is the eighth most frequent tumor and sixth leading cause of cancer death worldwide. Whereas the majority of cases occur in Asia, particularly in central China, recent data suggest that the frequency of new cases is rising in Western Europe and the USA [ 9 , 10 ]. Two major histological subtypes of esophageal cancer have been identified including squamous cell carcinoma (ESCC), which is more common in developing countries, and adenocarcinoma, which is more common in developed nations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer is the eighth most frequent tumor and sixth leading cause of cancer death worldwide. Whereas the majority of cases occur in Asia, particularly in central China, recent data suggest that the frequency of new cases is rising in Western Europe and the USA [ 9 , 10 ]. Two major histological subtypes of esophageal cancer have been identified including squamous cell carcinoma (ESCC), which is more common in developing countries, and adenocarcinoma, which is more common in developed nations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence rate of esophageal cancer is 3/10 5 person‐years in the US white population and reaches 1000/10 5 person‐years in some areas of China . The median survival time of patients with inoperable cancer is estimated to be only 13‐29 months, and the 5‐year survival rate of EC patients is only 10‐20% after radiotherapy or esophagotomy . These epidemiologic results reflect the low efficiency of current treatments, underscoring the need for a deeper understanding of the molecular mechanisms underlying this disease as well as for new therapeutic strategies for its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation at Serine 9 of GSK3β leads to a structural change and decreases its activity . PI3K activation results in Akt phosphorylation and the subsequent phosphorylation/inactivation of GSK3β, which has been demonstrated to suppress the production of pro‐inflammatory cytokines including IL‐12, TNFα, IL‐1β, IL‐6, IFNγ, and IL‐17, while it concurrently promotes the production of IL‐10, IL‐1Ra, and IFNβ by immune cells . Moreover, GSK3β is also involved in Wnt signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it has been previously demonstrated that SGK1 is associated with the progression of inflammation (2224), and inflammation per se has been demonstrated to be associated with the development of multiple types of cancer (25,26). A previous study demonstrated that active SGK1 decreases the production of pro-inflammatory cytokines, such as tumor necrosis factor, interleukin (IL)-12, and IL-1 (23).…”
Section: Discussionmentioning
confidence: 99%